Alexander Vatlin and Larisa Malashenko. Piggy Foxy and the Sword of Revolution. Bolshevik Self -Portraits - Былкова, В. (Інститут історії України НАН України, 2008)
Рецензія на книгу: Alexander Vatlin and Larisa Malashenko. Piggy Foxy and the Sword of Revolution. Bolshevik Self -Portraits / Translated from Russian by V.A. Staclo. Yale University Press New Haven & London, 2006. 206 p.